Gene drive behavior when pest populations have age, mating and spatial structure - Gould, Fred; Lloyd, Alun (Henry Stewart Talks, 2018)
Gene drive, Suppression drive, Transgenic gene drives, Level of detail in a model, Detailed model of Anopheles, Simple and complex models of other gene drives and gene drive reversal, Engineered under dominance, Age and spatial models, Spatial release models, Medea, Mosquito model in a dynamic city, Skeeter Buster